NATIONAL FEATURES AND DIFFERENCE OF ENGLISH AND UZBEK FOODS. - Saitmurodova Nozima Olim qizi,; Niyatova Maftuna Norbek qizi , (TADQIQOTLAR.UZ, 2023)
ANNOTATION :Nowadays cross-cultural interaction is developing rapidly and the influence of one culture to another is particularly significant in public life.The development of intercultural and international relationship gives the opportunity to be acquainted with different culture world. Especially, the fame question of our culture through translated artistic compositions is essential. Therefore, the translation of cultural phenomena plays a great role in everyday communication. National meals are also inseparable part of any culture or a nation. However, there are certain problems or obstacles while translating national meals in other languages. Realia can be used to overcome some difficulties and unfamiliarity of languages and cultures. From the etymological point of view the term of realia is taken from latin “realia” -“material”, “real living things” and realia means words and expressions for culture specific material things. They are things of material culture according to O. S. Axmanova in her book “Linguistic terms dictionary”. The Bulgarian translators Vlahov and Florin, who were the first to carry out an in-depth study of realia, coined the modern sense of the word. They indicate that since realia carry a very local overtone, they often pose a challenge for translation. Realia must not be confused with terminology: the latter is primarily used in the scientific literature to designate things that pertain to the scientific sphere, and usually only appears in other kinds of texts to serve a very specific stylistic purpose. Realia, on the other hand, are born in popular culture, and are increasingly found in very diverse kinds of texts. Fiction, in particular, is fond of realia for the exotic touch they bring